Farmacogenética de antirretrovirais em pessoas com HIV/AIDS - Luciana Cristina de Oliveira Cândido (2020)
One of the main challenges of antiretroviral therapy is its unpredictability and inter-individual variability in its outcome. The contribution of genetic, clinical and epidemiological variables as potential predictors of the response to antiretroviral therapy in patients with HIV/AIDS was investigated. Therefore, a systematic review with meta-analysis was carried out. In addition, 291 patients were genotyped for ABCB1 rs1045642, CYP2B6 rs3745274 and TNF-α rs1800629, rs361525 using Taqman probes. The results of the meta-analysis demonstrated an association between HLA-B*5701 and the hypersensitivity reaction to abacavir (O.R.=28.51; C.I.=9.95-81.71); ABCC4 rs1751034 and tenofovir-induced renal tubular dysfunction (O.R.=2.98; C.I.=1.41-6.28); CYP2B6 rs3745274 and central nervous system adverse effects to efavirenz (O.R.=2.10; C.I.=1.04-4.24); HLA-Cw*0401 (O.R.=2.98; C.I.=2.18-4.08) and HLA-DRB*01 (O.R=2.52; C.I.=1.29-4.91) and nevirapine-induced hypersensitivity reaction; and UGT1A1*28 and atazanavir-induced hyperbilirubinemia (O.R.=7.17; C.I.=4.32-11.91). The primary study revealed that 53% of the patients involved presented themselves late for care (CD4+ ≤350 cells/mm3). It was observed that of the individuals who started HAART with CD4+ ≤200, 350 and 500 cells/mm3, 58%, 45% and 38%, respectively, did not recover values above 500 cells/mm3. This study showed that males (p=0.02) and those at an advanced age at the time of diagnosis (p=0.01) were associated with lower CD4+ gain. The use of the TDF+3TC+EFZ scheme (p=0.03), protease inhibitors (p<0.0001) and tenofovir (p=0.0003) were associated with the increase in CD4+ count. The analysis showed that the polymorphisms analyzed are not associated with CD4+ dynamics during therapy. It is concluded that the area of pharmacogenetics provides evidence that can assist in directing therapeutic customization for the prescription of tenofovir, nevirapine and atazanavir. Late presentation to care is a major obstacle to the early onset of HAART, without which many do not recover immunity. If reaching values of 500 cells/mm3 of CD4+ causes the mortality rate to match that of the general population, this should be the goal of the clinic for all patients.